A Review of the Literature on Extrarenal Retroperitoneal Angiomyolipoma. (17th February 2016) - Venyo, Anthony Kodzo-Grey
Abstract : Background . Extrarenal retroperitoneal angiomyolipomas are rare. Aim . To review the literature. Results . Angiomyolipomas, previously classified as hamartomas, are now classified as benign tumours. Thirty cases of primary retroperitoneal angiomyolipomas have been reported. Diagnosis of the disease upon is based radiological and pathological findings of triphasic features of (a) fat and (b) blood vessels and myoid tissue. Immunohistochemistry tends to be positive for HMB45, MART1, HHF35, calponin, NKI-C3, and CD117. The lesion is common in women. Treatment options have included the following: (a) radical surgical excision of the lesion with renal sparing surgery or radical nephrectomy in cases where malignant tumours could not be excluded and (b) selective embolization of the lesion alone or prior to surgical excision. One case of retroperitoneal angiomyolipoma was reported in a patient 15 years after undergoing radical nephrectomy for angiomyolipoma of kidney and two cases of distant metastases of angiomyolipoma have been reported following radical resection of the tumour. Conclusions . With the report of two cases of metastases ensuing surgical resection of the primary lesions there is need for academic pathologists to debate and review angiomyolipomas to decide whether to reclassify angiomyolipomas as slow-growing malignant tumours or whether the reported cases of metastases were de novo tumours or metastatic lesions.